WIREGRID: A NEC2 PRE-PROCESSOR - Toit, C. F. du (Applied Computational Electromagnetics Society Journal (ACES), 2022)
WIREGRID is a pre-processor for the widely used public domain method of moments computer code NEC2. WIREGRID was developed for modelling metallic structures using a mesh of wires. In particular, it has powerful facilities for controlling the density of the mesh, permitting the same basic model to be used for different frequencies, with the code automatically generating a suitable mesh for a particular frequency. WIREGRID is not limited to generating wire meshes: it can also be usefully applied to true thin-wire modelling, for instance for Yagi-Uda and log-periodic antennas. In this paper, the basic philosophy of the code is described, and the code capabilities are detailed. Sufficient detail is presented so that the paper can serve as a reference for code users. The meshing algorithm is briefly described. An example is shown of the automatic mesh generation capabilities applied to an automobile. WIREGRID is available in the public domain via anonymous ftp; details of the ftp sites and hardware requirements are given in the appendices. [Vol. 10, No. 1 (1995), pp 31-39]